Modulation of the humoral immune response by constitutively active STAT6 expression in murine B cells - Haase, Paul; Mokada Gopal, Lavanya; Radtke, Daniel; Vöhringer, David (European Journal of Immunology, 2019)
The transcription factor STAT6 regulates gene expression in response to IL-4 and IL-13. To further investigate how activated STAT6 modulates B cells development and function in vivo, we characterized mice that express a constitutively active version specifically in B cells. CD19Cre_STAT6vt mice show spontaneous phosphorylation and nuclear translocation of STAT6 in B cells. About 80 genes were more than twofold up- or downregulated in splenic B cells from CD19Cre_STAT6vt as compared to control mice. B cell development, tissue localization, and populations of follicular and marginal zone B cells, B1 B cells, GC B cells, and plasma cells (PCs) appeared to be normal. However, the number of IgE(+) and IgG1(+) GC B cells and PCs as well as serum IgE and IgG1 levels were increased in CD19Cre_STAT6vt mice. Infection with Lymphocytic choriomeningitis virus associated with high levels of TNF and IFN-gamma did not prevent the development of a significantly increased IgE and IgG1 response against the virus in CD19Cre_STAT6vt mice. These results suggest that prolonged STAT6 activation during chronic allergic inflammation may result in IgE responses during subsequent viral or bacterial infection that could further stimulate mast cell activation even in the absence of the initial allergic response.
CRIS-Team WoS Importer:2019-12-27